OsLTP47 may function in a lipid transfer relay essential for pollen wall development in rice. (May 2022) - Chen, Libin; Ji, Chonghui; Zhou, Degui; Gou, Xin; Tang, Jianian; Jiang, Yongjie; Han, Jingluan; Liu, Yao-Guang; Chen, Letian; Xie, Yongyao
Abstract: In plants, lipid transfer proteins (LTPs) transport pollen wall constituents from the tapetum to the exine, a process essential for pollen wall development. However, the functional cooperation of different LTPs in pollen wall development is not well understood. In this study, we have identified and characterized a grass-specific LTP gene, OsLTP47, an important regulator of pollen wall formation in rice ( Oryza sativa ). OsLTP47 encodes a membrane-localized LTP and in vitro lipid-binding assays confirms that OsLTP47 has lipid-binding activity. Dysfunction of OsLTP47 causes disordered lipid metabolism and defective pollen walls, leading to male sterility. Yeast two-hybrid and pull-down assays reveal that OsLTP47 physically interacts with another LTP, OsC6. These findings suggest that the plasma membrane-localized OsLTP47 may function as a mediator in a lipid transfer relay through association with cytosolic and/or locular OsC6 for pollen wall development and that various LTPs may function in a coordinated manner to transport lipid molecules during pollen wall development.